The Effect of Discovery Learning on the Problem Solving Ability and Science Learning Outcomes in Elementary School Students - Rosmala Rosmala; Abdul Rahman; Dody Sukmayadi (EduLine: Journal of Education and Learning Innovation, 2023)
Learning should develop human potential, one of which is the ability to solve problems in addition to the success of a learning process, namely learning outcomes. Discovery learning is a learning model that can be applied to develop this. The purpose of conducting the following research was to analyze the effect of discovery learning on problem solving abilities and learning outcomes of elementary school students. Through the experimental method with a quasi-experimental type that compares the experimental class and the control class. Data were collected using a test instrument for problem solving abilities and learning outcomes given before and after treatment for both classes. Based on data analysis, the value of sig.(2-tailed) = 0.000 <0.05 for both tests on the variables of problem-solving ability and learning outcomes so that it can be concluded that the discovery learning model influences problem-solving abilities and learning outcomes of fifth grade elementary school students